2013
DOI: 10.1037/a0030108
|View full text |Cite
|
Sign up to set email alerts
|

Messages for men: The efficacy of EPPM-based messages targeting men's physical activity.

Abstract: From these results, we suggest preliminary recommendations for the development of physical activity messages for men and areas for future EPPM-based research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…Men also tend to underestimate their health risks, which can lead to avoidance and reactance toward traditional risk information messages; however, despite these differences, little is known about effective gender-specific health communication strategies [55]. …”
Section: Introductionmentioning
confidence: 99%
“…Men also tend to underestimate their health risks, which can lead to avoidance and reactance toward traditional risk information messages; however, despite these differences, little is known about effective gender-specific health communication strategies [55]. …”
Section: Introductionmentioning
confidence: 99%
“…Little male-specific research has been undertaken, and best practice approaches have not been identified [12,14,15]. Overall, males receive less educational advice than women from health professionals about modifiable lifestyle behaviors associated with disease risk [16], and there are a lack of resources available that are targeted specially at males [17,18]. There is strong evidence that behavior change interventions that address characteristics and behavior change determinants unique to particular subgroups are more effective than generic “one-size-fits all” approaches [19].…”
Section: Introductionmentioning
confidence: 99%
“…Men have higher rates of physical inactivity, poor nutrition, and excessive alcohol consumption than women, coupled with the fact that they are resistant to engaging with the health-care system or participating in preventative health practices. [25][26][27][28][29][30][31] The association between metabolic dysfunction and urologic disorders such as lower urinary tract symptoms, low testosterone, and erectile dysfunction is becoming more clearly ingrained in urologists' minds. [32][33][34] As perhaps the only physicians, aside from our colleagues in primary care, who see men presenting with these issues, urologists have the opportunity to expand their awareness of systemic diseases and institute prevention, screening, and treatment programmes.…”
Section: What Comprises Men's Health?mentioning
confidence: 99%